Analysis of coconut shell adsorption capability as greywater waste adsorbent - Devy Cendekia; Dian A Afifah (Jurnal Teknik Kimia, 2024)
As coconut plantations increase in Indonesia, coconut shell waste has the potential to damage the environment if it is not processed properly. Various studies state that coconut shell waste can be used as a greywater adsorbent. Greywater is a domestic waste that is much less polluted than domestic wastewater because it does not contain urine, feces, and toilet paper, and only contains about 30% of the total organic load. Therefore, it is important to determine the right adsorbent for appropriate processing. So this research will test the adsorption capacity of coconut shell waste as a greywater adsorbent using iodine absorption analysis. In the analysis of iodine absorption capacity, coconut shell adsorbents have high adsorption capabilities in absorbing adsorbate (iodine molecules) with high molecular concentrations. Based on iodine absorption analysis data, it is known that the coconut shell waste adsorbent has a maximum adsorption capacity of 2.86 x 10-3 mg g-1 by following the Langmuir isotherm model. The coconut shell waste adsorbent used as a medium in the adsorption column was able to reduce total dissolved solids by 3.7 %, total suspended solids by 23.3 %, and phosphate removal efficiency by 6.3 % in greywater waste samples. This proves that coconut shell waste can act as an adsorbent in managing greywater waste.